Efficiency of a triangular solar still integrated with external PVC pipe solar heater and internal separated condenser - Emran, N.Y.Y. (Elsevier Ltd, 2022)
Modern designs of solar still desalination technology are reported to tackle the cost and energy issues. However, the low productivity of this technology is the main challenge that inhibits its commercialization uses. In this study, a triangular solar still (TrSS) integrated with an external PVC pipe solar heater and an internal separated condenser is designed for the first time to enhance water desalination under Malaysian climate conditions. The daily water production of active still was 24 higher than that of passive one. The temperatures of water and ambient air, relative humidity inside the still and the intensity of solar radiation affect the daily distillate output of both stills. Besides, a few strong relationships were developed between the intensity of solar radiation and water productivity, between the daily average ambient temperature and water productivity, and between the daily average water temperature and water productivity. The desalinated water cost per liter is estimated and is reasonable. Finally, the water quality tests of raw seawater and product water were performed and analyzed. A significant improvement in the desalinated water quality is realized when compared with raw seawater quality. The product water was considered as safe drinkable water while comparing its quality with the World Health Organization (WHO) standards. Â© 2022 Elsevier Ltd